Bay Leaf Extract as a Potential Therapeutic Agent for LDL Reduction in Hypercholesterolemia: A Dose-Response Study - Sudarmika, Kadek Adi; Putu Oky Ari Tania (HM Publisher, 2024)
Hypercholesterolemia, characterized by elevated low-density lipoprotein (LDL) cholesterol levels, is a major risk factor for cardiovascular disease. The current study investigated the dose-dependent effects of bay leaf extract on LDL cholesterol reduction in a hypercholesterolemic rat model. Male Wistar rats were fed a high-fat diet to induce hypercholesterolemia. They were then randomly assigned to five groups: positive control (simvastatin), negative control (standard diet), and three treatment groups receiving graded doses of bay leaf extract (0.72 g, 1.08 g, and 1.80 g). LDL cholesterol levels were measured after seven days of treatment. Bay leaf extract administration resulted in a dose-dependent reduction in LDL cholesterol levels. The highest dose (1.80 g) exhibited comparable efficacy to simvastatin in lowering LDL cholesterol. In conclusion, bay leaf extract demonstrates potential as a therapeutic agent for managing hypercholesterolemia by effectively reducing LDL cholesterol levels. The optimal dose for LDL reduction appears to be 1.80 g. Further research is warranted to explore the underlying mechanisms and clinical implications of these findings.